Psalmen- und Psalter-Rezeption im Frühjudentum : Rekonstruktion, Textbestand, Struktur und Pragmatik der Psalmenrolle 11QPsa aus Qumran - Dahmen, Ulrich, 1961- (Studies on the Texts of the Desert of Judah, 2003)
This volume is concerned with the great Psalms Scroll from cave 11 at Qumran as an example for the reception (\'Fortschreibung\') of biblical texts and books in early judaism. After methodological considerations the scroll is examined and reconstructed entirely in its material and textual extent for the first time. Detailed analyses of the text and the structure of this work show that 11QPsᵃ developed from the final redaction of the biblical book of Psalms. In its unique text form and arrangement of Psalms it was composed in a qumranic milieu and functions as a work for a davidic figure.